Art as a Strategy to Make Possible the Reparation of the Damage Derived from the Internal Armed Conflict: El arte como estrategia para viabilizar la reparación del daño producto de confrontaciones bélicas internas - Sánchez, Jenny; Pabón, Patricia; Aguirre, Javier (Revista de Filosofía, 2022)
The peace processes have incorporated transitional justice spaces that seek to repair, by alternate means, the damage and effects derived from the internal armed conflict. In this sense, it is necessary to inquire about what mechanisms make reparation possible within the framework of transitional justice and the post- agreement stage? This text suggest some reflections from the analysis of the experiences of women who, through art, have developed strategies to make reparation viable, to explore their potential and difficulties.